Respuesta :

Answer:

h(2) = 7/4

h(-3) = -2

h(-2) = 11/(-8)

h(-3) - h(-2) = -(5/8)

Step-by-step explanation:

h(x) = (2x^2-x+1) / (3x-2)

h(2) = (2*2^2 - 2 + 1) / (3*2 - 2)

       = (8 - 2 + 1) / (6 - 2)

       = 7/4

h(-3) = {2*(-3)^2 - (-3) + 1} / {3*(-3) - 2}

        = (18 + 3 + 1) / (-9 - 2)

        = 22/(-11)

        = -2

h(-2) = {2*(-2)^2 - (-2) + 1} / {3*(-2) - 2}

        = (8 + 2 + 1) / (-6 - 2)

        = 11/(-8)

h(-3) - h(-2) = (-2) - {11/(-8)}

                  = -(5/8)

Hope this will help. Please give me brainliest.

[tex]h(3) - h( - 2) = - \frac{5}{ 8} \\ \\ [/tex]

[tex]\boxed{h(x) = \frac{2 {x}^{2} - x + 1}{3x - 2}}[/tex]

[tex]h(2) = \frac{2 {(2)}^{2} - (2) + 1}{3(2) - 2} [/tex]

[tex]h(2) = \frac{2 {(4)} - 2 + 1}{6 - 2} [/tex]

[tex]h(2) = \frac{ 8 - 1}{4} [/tex]

[tex]h(2) = \frac{7}{4}[/tex]

[tex]h( - 3) = \frac{2 {( - 3)}^{2} - ( - 3) + 1}{3( - 3) - 2} \\ h( - 3) = \frac{2 (9) + 3 + 1}{ - 9- 2} \\ h( - 3) = \frac{18 + 4}{ - 11} \\ h( - 3) = \frac{22}{ - 11} \\ h(-3) = -2[/tex]

[tex]h( - 2) = \frac{2 {( - 2)}^{2} - ( - 2) + 1}{3( - 2) - 2} \\ h( - 2) = \frac{2 (4) + 2+ 1}{- 6 - 2} \\ h( - 2) = \frac{8 + 3}{- 8} \\ h( - 2) = \frac{11}{- 8} [/tex]

[tex]h(3) - h( - 2) = -2 - \frac{11}{- 8} \\=-2 + \frac{11}{ 8} \\ =- \frac{5}{ 8} [/tex]